A longitudinal modelling study estimates acute symptoms of community acquired pneumonia recover to baseline by 10 days. Issue 6 (15th June 2017) - Wootton, Daniel G.; Dickinson, Laura; Pertinez, Henry; Court, Joanne; Eneje, Odiri; Keogan, Lynne; Macfarlane, Laura; Wilks, Sarah; Gallagher, Jane; Woodhead, Mark; Gordon, Stephen B.; Diggle, Peter J.
Our aims were to address three fundamental questions relating to the symptoms of community-acquired pneumonia (CAP): Do patients completely recover from pneumonia symptoms? How long does this recovery take? Which factors influence symptomatic recovery? We prospectively recruited patients at two hospitals in Liverpool, UK, into a longitudinal, observational cohort study and modelled symptom recovery from CAP. We excluded patients with cancer, immunosuppression or advanced dementia, and those who were intubated or palliated from admission. We derived a statistical model to describe symptom patterns. We recruited 169 (52% male) adults. Multivariable analysis demonstrated that the time taken to recover to baseline was determined by the initial severity of symptoms. Severity of symptoms was associated with comorbidity and was inversely related to age. The pattern of symptom recovery was exponential and most patients' symptoms returned to baseline by 10 days. These results will inform the advice given to patients regarding the resolution of their symptoms. The recovery model described here will facilitate the use of symptom recovery as an outcome measure in future clinical trials. Severity of CAP symptoms is inversely related to age and resolution to baseline symptoms takes on average 10 days http://ow.ly/dV0h30befE3